The Walkability Concept in Jurnatan as A Buffer Area of Kota Lama Semarang - Nindita Kresna Murti; Kania Kinasih; Huda Muhammad Basalamah; Deni Wahyu Setiawan; Alfanadi Agung Setiyawan (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2019)
Jurnatan area is a trading and office hub in Semarang City which was built in the 1970s. Furthermore, the area is directly adjacent to Semarang’s premier cultural heritage area, namely Kota Lama. Since the economic center shifted to the Simpang Lima area in the 1980s, Jurnatan area lost its chief appeal, and was gradually abandoned. This heavily impacted the area, resulting in abandoned complexes, declining trade, and its current status as a ‘no man’s land’. This study aims to find design concepts to revitalize the area, and revitalize its function as an area which supports the area of Kota Lama Semarang, in its ambition to become a World Heritage site. The area planning forwards the concept of walkability, which puts pedestrian needs ahead of vehicles. Besides being an important part of the Semarang City Government’s plan to revitalize the Kota Lama, this concept is suitable for reducing the density of vehicles both in the cultural heritage area and the transition area of shopping complex.